KESALAHAN PENGGUNAAN HURUF KAPITAL, KATA DEPAN, DAN TANDA BACA DALAM SURAT DINAS DI KANTOR POLISI RESOR SIAK - Sianturi, Evi Kristin; Sinaga, Mangatur; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Misuse of capital letters, forecasts, and punctuation is a very important thing to note as it relates to the meaning and message to be conveyed to the reader. At Siak Siak Police Station Siak Sri Indrapura there is a misuse of punctuation, foreword, and punctuation. The purpose of this study is to determine the use of capital letters, foreclosures and punctuation in the official service in Siak Police Siak Si Indrapura Regency. Data collection techniques using descriptive method to illustrate the use of capital letters, forecasts, and the use of punctuation in the official service in Siak District Police Station Siak Sri Indrapura Regency. Based on the research, the authors found 67 misuse of capitalization, 17 front-word errors, and 68 punctuation errors.Keywords: capital letters, forecasts, and punctuation.